The inclusion of primary care physicians in pandemic flu planning: An analysis of historical lessons and current issues - Lauer, Jacob K. (My University, 2008)
A paper presented to the College of Agriculture Honors Committee of Kansas State University in partial fulfillment of requirements for the Honors Program of Kansas State University.
Keywords: Influenza; Pandemic; Physicians; 1918 flu; Public health; Preparedness